Strengthening National Defence: Coordinating Waters and Air Territory Security under the Indonesian National Police - Abdul Rahman; Saleha Mufida; Dian Handayani; Wavin Nuha Kuntanaka (Journal of Maritime Studies and National Integration, 2021)
This study aims to analyse the role of a corps under the Indonesian National Police, known as Air and Water Police Corps (Ditpolair Korpolairud Baharkam) to strengthen national defence. Being on the equator makes Indonesia rich in natural resources, but, its strategic position also poses a threat, especially in the defence and security sector in border areas, both regional and international trade routes. The actual threats at trade crossings where about 40% of trade routes pass through Indonesia are the high cases of smuggling of illegal goods, human trafficking, illegal fishing, and many other cases that occur in Indonesian waters. In accordance with Article 6 of Law Number 34 Year 2004 that the Indonesian Navy as the main component functions as an antidote, act and restore the condition of state security. The Indonesian Navy as a Military Defence Force has a heavy role because as a military, police, diplomacy and support, it also functions as a marine controller and power projection. While Non-militer Defence entities such as the National Police, Indonesian Ministry of Marine and Fisheries Affairs (KKP), Indonesian Maritime Security Agency (Bakamla) as the coordinator. The normative juridical approach has been used and qualitative research methods are explained in descriptive analysis. The result shows that Ditpolair Korpolairud Baharkam carried out their roles as mandated by laws and regulations and the need for communication and coordination in synergy with all defence forces handling maritime, so that the integrity of Indonesia remained intact.